EWOLUCJA ODPOWIEDZIALNOŚCI WŁADZY PUBLICZNEJ - OD WINY FUNKCJONOWANIA DO BEZPRAWNOŚCI NORMATYWNEJ - Safjan, Marek (Zeszyty Prawnicze, 2017)
Evolution of Liability of Public Authorities - from Guilt of Functioning to Normative Lawlessness Summary The above discourse supports a general thesis that the approach to the principles behind the liability of public authorities is an important indicator of the democratic system, and for assessment of relations between public authorities and citizens. The evolution of these principles in the Polish law corresponds to the history of the evolution of the political system over the last few decades. Nevertheless, it appears that the last fundamental changes in the field of public liability pushing it towards greater objectiveness, still do not remove many significant questions and dilemmas, which are still waiting to be solved. A real antinomy between protection of individual interests, and the general interest becomes more and more acute. Thus, the need is and will be growing to find answers to the complicated problems of statutory unlawfulness. Without doubt, the existence in the legal system of constitutional courts is an important, may be even the most important factor and the point of reference for any analysis made in this field. Possibly, we are approaching a breakthrough in the field of liability of the public authorities. The need for an in-depth reflection over these issues becomes increasingly pressing.